School Counselor Preparation to Support Inclusivity, Equity and Access for Students of Color With Disabilities - Reese, Diane M. (Frontiers in Education, 2021)
The effective implementation of comprehensive school counseling services to all students is premised on the ASCA National Model framework themes of leadership, advocacy, collaboration, and systemic change. The school counselor’s role is to support the academic, career and social-emotional development of all students. From a school counselor advocacy and social justice perspective, school counselors engage in practices that will support all students and create opportunities for equal access and success through their leadership and service as collaborators, consultants and change agents. School counselor leadership results in positive changes within the school community. Using the ASCA Model Framework themes, school counselors can integrate these themes to support inclusivity, equity and access for students of color with disabilities, to the general education curriculum. In order to better prepare school counselor trainees to provide culturally appropriate support and services for students of color with disabilities, school counselor education programs must be more intentional in providing graduate-level course work that introduces trainees to best practices in their work with students with disabilities. First, this writer will discuss the ethical imperative for school counselor educators to be intentional in integrating special education curriculum in preparation programs and how school counselor education programs can use the ASCA Model framework themes in preparing school counselor trainees to engage in best practices to encourage, support, and ensure that students of color with disabilities have access and inclusion in the general education settings. Secondly, this writer will also discuss the incorporation of interactive related ASCA theme activities as preparation for school counselor trainees, in a special topics course as well as during practicum and internship and future professional school counselor opportunities.